Design and Simulation of a New ZVT Bi-directional DC-DC Converter for Electric Vehicles - Rajesh Thumma; Veera Venkata Subrahmanya Kumar Bhajana; Pramo kumar Aylapogu (Institute of Advanced Engineering and Science, 2017)
This paper presents a new zero voltage transistion (ZVT) bi-directional DC-DCconverter for energy storage system in DC traction. This bidirectional converter can transfers the power flow from low voltage side to high voltage side and viceversa. The conventional hard-switched non-isolated converter improved with the additional auxiliary cell to obtain zero voltage transition for the IGBTs. The main advantages of this topology are reduced the switching losses and improved the efficiency as well.The main aim of this converter is to achieve the operation of zero voltage transition during the commutation of main switches from off to on by utilizing auxiliary cell, which consist active and passive elements.The boost and buck modes of operations are achieved with the zero voltage transistion, which reduce the IGBTs current stresses and switching losses.This paper mainly describes the operation principles and the evaluation of the simulation results with the aid of Matlab simulations.The obtained results were proved the expected assumptions of the theoretical analysis.